MORAL THEOLOGY AT THE DAWN OF VATICAN II: A BRIEF PRESENTATION OF ARREGUI-ZALBA’S COMPENDIO DE TEOLOGÍA MORAL - Lasheras, Diego Alonso (Asian Horizons, 2015)
The article offers an overview of the Compendio de teología moral by Arregui-Zalba, a very significant work of moral theology (particularly in the Spanish speaking world) in the years preceding Vatican II. The overview presents the structure of the book, some of the main characteristics of its way of doing moral theology and a few examples of particular topics. The article helps us understand the directions of pre-conciliar moral theology. 50 years after Vatican II, the aim of the article is to help to understand the significance and the effects of the Council in the renewal of moral theology, particularly the significance and timeliness of the call of Optatam Totius, 16 to give special care to the perfection of moral theology, which “nourished more on the teaching of the Bible, should shed light on the loftiness of the calling of the faithful in Christ and the obligation that is theirs of bearing fruit in charity for the life of the world.”